O legislador: da crítica ao formalismo conceitual para início de consciência sobre legisgênese - Cavalcanti, Avner Pinheiro (2016)
The paper presents the bases for a theory of how the rules of law are formed, based on the only concept of substantive law already outlined, by Claudio Souto. According to the said author, Law is the externalization of the human feeling of being-oriented by the currently insuperable information or, simplifying, the compound SIV (Feeling, Idea and Will). The existence of this intrinsic feeling to the human condition has already been empirically proven by the work of Paul Bloom. However, further details, such as the proof of Claudio Souto's theory for Paul Bloom's work and the confirmation of the theory that will be presented, are scheduled for the next work, in Doctorate Degree. In the present work we present the fundamental bases of what has come to be called by us of “Legisgênesis” or the human social phenomenon of the configuration of the duty-to-be. This phenomenon differs from the legislator considered by the legal tradition, it is that it is exclusively formalist. The legislator idealized by tradition can be divided into two genres: legislator stricto sensu and legislator lato sensu. By legislator stricto sensu we mean the official agents responsible for drawing up the equally official laws and by legislator stricto sensu the strategies of argumentation, by rationalization, used in legal practice. These genre, on the other hand, present subdivisions in species that we classify and try to explain in the course of the present work.The fundamental difference between the conceptions raised is established between what can be called a formal legislator (legal myth) and real legislator (human phenomenon). Formal legislator, understood as the source of rules and law, is a modern legal myth about which a reality is artificially created, a reality that corresponds to what tradition calls the legal world. The real legislator, or rather, the legislature, takes care to explain how human societies formulate imperatives of conduct classifiable as Law. In order to allow and explain this fundamental difference and the reasons that hold the myth of the legislator in force, we are concerned with explaining the political and philosophical reasons why law has been operated through rhetoric in order to provide official leaders with a Mechanism of social control. The main purpose of the paper was to answer the question: if the law is admittedly prior to the laws formulated by the official authorities, who or what is the legislator in fact? The result was what we call the Theory of Legislation. The method used was transdisciplinary, correlating works and theses, from different areas, in order to configure a theory, or rather, the basis of a new theory in response to the problem.